Dry Eye as a Mucosal Autoimmune Disease. (13th January 2013) - Stern, Michael E.; Schaumburg, Chris S.; Pflugfelder, Stephen C.
<x xml:space="preserve">Abstract</x> Dry eye is a common ocular surface inflammatory disease that significantly affects quality of life. Dysfunction of the lacrimal function unit (LFU) alters tear composition and breaks ocular surface homeostasis, facilitating chronic inflammation and tissue damage. Accordingly, the most effective treatments to date are geared towards reducing inflammation and restoring normal tear film. The pathogenic role of CD4+ T cells is well known, and the field is rapidly realizing the complexity of other innate and adaptive immune factors involved in the development and progression of disease. The data support the hypothesis that dry eye is a localized autoimmune disease originating from an imbalance in the protective immunoregulatory and proinflammatory pathways of the ocular surface.